Respuesta :

Answer:

C) -2a-12

Step-by-step explanation:

you use the distributive property so you multiply -2 by a and 6

(-2)(a) + (-2)(6)

-2a-12

Answer:

-2a-12

Step-by-step explanation:

From Distributive Property, states that:

[tex] \displaystyle \large{x(b + c) =x b + xc}[/tex]

Compare the number/term, we can say that:

  • x = -2
  • b = a
  • c = 6

Substiture these values in.

[tex] \displaystyle \large{ - 2(a + 6) = - 2 a - 2(6)} \\ \displaystyle \large{ - 2(a + 6) = - 2 a -12}[/tex]

And we're done!